Description of 33 new species of Calamoceratidae, Molannidae, Odontoceridae and Philorheithridae (Trichoptera), with detailed presentation of their cephalic setal warts and grooves - Oláh, János; Johanson, Kjell Arne (Zootaxa, 2010)
Additions to the taxonomy of the leptoceroid families Calamoceratidae, Molannidae, Odontoceridae, and Philorheithridae are given, and 33 new species in the superfamily are described based on characters in the male genitalia, head and thoracal setose warts, and groove patterns, wing venation, and forewing colour and pattern. In the Calamoceratidae Ulmer, the Anisocentropus latifasciata diagnostic species-group and Anisocentropus brevipennis diagnostic species cluster are described for the first time. The following 17 species are described as new: Anisocentropus bungus (Vietnam), A. csorbai (Vietnam), A. dvaupadhah (Malaysia), A. fridae (Fiji Islands), A. hannahae (Fiji Islands), A. hoisat (Laos PDR), A. malaisei (Myanmar), A. maralus (Malaysia), A. mjoebergi (Borneo), A. samuh (Madagascar), A. tapenan (Solomon Islands), A. thinlin (Laos PDR), A. thonmihn (Vietnam), A. vanuensis (Fiji Islands), A. vitiensis (Fiji Islands), Ganonema malickyi (Thailand) and G. rong (Vietnam). In addition, Ganonema fuscipenne (Albarda) is synonymized with G. ochraceellum (McLachlan), and Ganonema pallidum Martynov is synonymized with Anisocentropus kawamurai (Iwata). In the Molannidae Wallengren, a single new species, Molanna gamdaha, is described from Myanmar. In the Odontoceridae Wallengren, the genus Inthanopsyche Malicky is synonymized with Psilotreta Banks. The following 14species belonging to previously described genera, are described as new: Lannapsyche birathena (Myanmar), L. suksma (Myanmar), L. kamba (Myanmar), Marilia enikiana (Laos PDR), M. jonssoni (Laos PDR), M. katakaha (Malaysia), M. malickyi (Laos PDR, Malaysia, Vietnam), M. mendolonga (Malaysia), M. namha (Laos PDR), M. tuyetmira (Laos PDR), Phraepsyche pectinata (Vietnam), P. yitungshana (China: Hong Kong), Psilotreta enikoae (Vietnam), and P. malickyi (Myanmar). In addition, the following 3 diagnostic species-groups are described for the first time: Psilotreta japonica diagnostic species-group, Psilotreta trimeresuri diagnostic species-group, and Psilotreta frontalis diagnostic species group. The species Ganonema odaenum Kobayshi is synonymized with Psilotreta locumtenens Botosaneanu, and Psilotreta pyonga Oláh is synonymized with P. falcula Botosaneanu. In the Philotheithridae Mosely, a single new species, Psilopsyche granda, is described from Chile. In addition to describing new taxa, new species records for 34 species in the superfamily are presented.